Sensory interaction between 3‐mercaptohexan‐1‐ol and 2‐isobutyl‐3‐methoxypyrazine in dearomatised Sauvignon Blanc wine. (June 2014) - van Wyngaard, E.; Brand, J.; Jacobson, D.; du Toit, W.J.
Abstract Background and Aims Two compounds that play an important role in the aroma of Sauvignon Blanc wines are 3‐mercaptohexan‐1‐ol (3MH) and 2‐isobutyl‐3‐methoxypyrazine (IBMP). Little is known about the sensory interaction of these two compounds in Sauvignon Blanc wine and which aroma attributes they elicit at the concentration range normally found in Sauvignon Blanc wines. Methods and Results 3‐Mercaptohexan‐1‐ol and IBMP were spiked separately or as a mixture to dearomatised Sauvignon Blanc wine at five different concentrations normally occurring in wine, and were assessed by a trained sensory panel. Descriptors were generated by the panel for these compounds when added alone, with overall tropical, guava and passionfruit being generated for 3MH, while overall green, green pepper and grass were used for IBMP. The contribution of these attributes differed, however, depending on the concentration of 3MH and IBMP. Conclusions There is sensory interaction between 3MH and IBMP. The sensory attributes linked to each compound can depend on the concentration of both compounds present in wine. It is possible that wine producers may use this phenomenon to achieve a specific style of Sauvignon Blanc wine. Significance of the Study This study might allow wine producers to predict which aroma profile to expect when 3MH and IBMP occur at a certain concentration in Sauvignon Blanc wine.